Exploring the Impact of Exercise Motivation and Perceived Health Competence on Emotional Eating - Muñoz, Nayelli; Abalorio, Bridget (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective:  This study aims to investigate the relationships between emotional eating, exercise motivation, and perceived health competence among adults.Methods and Materials: The study employed a cross-sectional design with a sample of 193 adults, determined based on the Morgan and Krejcie table. Participants completed validated questionnaires measuring emotional eating, exercise motivation, and perceived health competence. Data were analyzed using Pearson correlation to assess the relationships between variables and multiple linear regression to determine the predictive power of exercise motivation and perceived health competence on emotional eating. All statistical analyses were conducted using SPSS version 27.Findings:  The regression analysis indicated that exercise motivation and perceived health competence together explained 29% of the variance in emotional eating behaviors (R² = 0.29, adjusted R² = 0.28, F(2, 190) = 39.75, p < .001). Both exercise motivation (B = -0.40, p < .001) and perceived health competence (B = -0.35, p < .001) were significant predictors of emotional eating.Conclusion: The findings suggest that higher levels of exercise motivation and perceived health competence are associated with lower levels of emotional eating.